The transformation myth: leading your organization through uncertain times - Gerald, Kane. (Cambridge The Mit Press, 2021)
When COVID-19 hit, businesses had to respond almost instantaneously--shifting employees to remote work, repairing broken supply chains, keeping pace with dramatically fluctuating customer demand. They were forced to adapt to a confluence of multiple disruptions inextricably linked to a longer-term, ongoing digital disruption. This book shows that companies that use disruption as an opportunity for innovation emerge from it stronger. Companies that merely attempt to "weather the storm" until things go back to normal (or the next normal), on the other hand, miss an opportunity to thrive.
Includes bibliographical references (pages 205-216) and index.
Keywords: Crisis management